BORON AND FLUORINE IN THE LITHOSPHERE OF THE PAMIRS AND TIEN SHAN, TAJIKISTAN: A GEOCHEMICAL LINKAGE BETWEEN THE MANTLE AND CRUST - Lutkov V.S.; Mogarovskii V.V.; Lutkova V.Ya. (My University, 2004)
The concentrations of B, F, and other "crustal" elements (Li, Sn, Rb, and Cs) in some mantle-derived rocks from the Pamirs and Tien Shan are higher than in the Earth's crust. In the mantle F is largely related to K being incorporated into phlogopite produced by modal metasomatism, whereas B is associated with Mg (olivine) and probably characterized by a nonstructural distribution caused by cryptic metasomatism. It is suggested that the mantle was the major or an additional source of the lithophile trace elements not only during formation of the major volume of the Neoarchean-Paleoproterozoic continental crust of the region but also in the Phanerozoic (metasomatic zones in the crust and mantle, rare-metal granites, and B and F deposits . Some common geochemical features of the regional lithosphere can be attributed to the influence of long-lived sub-lithospheric fluid and melt flows.